The relationship of Father’s involvement in parenting and emotional maturity with self-regulation in college students - Khannia Hannidhita Adelina; Aditya Dedy Nugraha (Universitas Sarjanawiyata Tamansiswa, 2026)
Students are required to be independent and able to face various new challenges, both academically, emotionally, and socially. Therefore, self-regulation is important for managing oneself and surviving in the face of life's pressures. This study aims to determine the relationship among father involvement in parenting, emotional maturity, and self-regulation in students. The study employs a quantitative correlational method using the Short Regulation Scale (SSR), the Father Involvement Scale, and the Emotional Maturity Scale as measurement tools. The sample consists of 400 college students aged 18–25 years who still have a father, reside in the area, and are actively enrolled at one of the universities in DIY, selected through purposive sampling. The results indicate that both father involvement and emotional maturity are positively and significantly related to self-regulation. Notably, emotional maturity emerged as a stronger predictor compared to father involvement. These findings suggest that while paternal support remains relevant, emotional development plays a more dominant role in enhancing self-regulation among young adults. The study emphasizes the importance of educational and family interventions that foster emotional maturity alongside father involvement to support students’ self-regulatory capacities